KOMUNIKASI PARIWISATA DINAS PENDIDIKAN DAN KEBUDAYAAN DALAM MEMPROMOSIKAN MUSEUM TUANKU IMAM BONJOL SEBAGAI DESTINASI WISATA SEJARAH DI KABUPATEN PASAMAN - Mufeldo Prakasa Nenggala; Muhammad Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Tuanku Imam Bonjol Museum is one of the places visited by many tourists because it has good and strong potential and attraction to attract tourists so that this historical tourist attraction is prioritized in its development and as a mainstay of tourist attraction in Pasaman Regency. So the author is interested in conducting a research entitled